Sustainable Infrastructure Systems: Bridging Transportation Efficiency, Structural Resilience, and Environmental Management - Reza Pahlevi Munirwan; Ramadhansyah Putra Jaya; Aizat Mohd Taib (Disaster in Civil Engineering and Architecture, 2026)
Sustainable infrastructure has emerged as a central pillar in addressing the complex challenges associated with rapid urbanization, population growth, and climate variability. Modern civil engineering practice increasingly demands integrated solutions that not only enhance system performance but also balance environmental responsibility, user satisfaction, and long-term resilience. Within this context, the convergence of transportation efficiency, structural reliability, and environmental sustainability forms a critical foundation for future infrastructure development. This Volume 3, Number 1 (April 2026) brings together a diverse set of studies that collectively reflect the multidisciplinary nature of contemporary infrastructure research. Several contributions focus on transportation systems, highlighting the importance of data-driven approaches in optimizing operational performance and user experience. From traffic signal optimization using analytical models to service quality assessment of transport hubs such as ferry ports and passenger terminals, these studies emphasize the role of user-centered design and performance evaluation frameworks in improving mobility systems.